Anisometric brain dimorphism revisited: Implementation of a volumetric 3D standard brain in Manduca sexta. - El Jundi, B; Huetteroth, W; Kurylas, A; Schachtner, J (2009)
Lepidopterans like the giant sphinx moth Manduca sexta are known for their conspicuous sexual dimorphism in the olfactory system, which is especially pronounced in the antennae and in the antennal lobe, the primary integration center of odor information. Even minute scents of female pheromone are detected by male moths, facilitated by a huge array of pheromone receptors on their antennae. The associated neuropilar areas in the antennal lobe, the glomeruli, are enlarged in males and organized in the form of the so-called macroglomerular complex (MGC). In this study we searched for anatomical sexual dimorphism more downstream in the olfactory pathway and in other neuropil areas in the central brain. Based on freshly eclosed animals, we created a volumetric female and male standard brain and compared 30 separate neuropilar regions. Additionally, we labeled 10 female glomeruli that were homologous to previously quantitatively described male glomeruli including the MGC. In summary, the neuropil volumes reveal an isometric sexual dimorphism in M. sexta brains. This proportional size difference between male and female brain neuropils masks an anisometric or disproportional dimorphism, which is restricted to the sex-related glomeruli of the antennal lobes and neither mirrored in other normal glomeruli nor in higher brain centers like the calyces of the mushroom bodies. Both the female and male 3D standard brain are also used for interspecies comparisons, and may serve as future volumetric reference in pharmacological and behavioral experiments especially regarding development and adult plasticity. J. Comp. Neurol. 517:210-225, 2009. (c) 2009 Wiley-Liss, Inc.